Performance appraisal of the Frontline Extension System in north eastern region of India: A policy imperative - PAUL, S; TRIPATHI, A K; BURMAN, R R; SINGH, A K (The Indian journal of agricultural sciences, 2016)
The difficulty prone and disadvantageous areas of the country, generally being untouched and unreached in terms of efficient execution of agricultural development programmes and policy measures, the frontline extension set-up is expected to be effective enough to voice and take over development issues of the inhabitant peasants. Concurrent to the concern, the present study aimed at a functionary level performance appraisal of the frontline extension system in north eastern region of India with a sample size of 231 Subject Matter Specialists (SMSs) from 59 Krishi VigyanKendras (KVKs) across the eight north eastern states. A principal component analysis based Composite Job Performance Index (CJPI) was developed to measure performance of the respondent SMSs in different job areas. The study revealed that the human resource development and organizational development intervention for harnessing optimum performance of the SMSs require immediate emphasis. The overall performance in the area of field crop production and improvement was the best among the seven thrust areas identified under the study, although performance in extension and communication modelling generated real concern as per the CJPI. A regression analysis depicted that gender, physical facilities, support and professional mentorship received from the host institute, and participation in knowledge sharing forums had significant association with job performance. Timely and adequately funding the KVKs for infrastructure development is crucial along with wilful self-updating and self-development on the part of the functionaries for harnessing optimum individual performance and thereby overall functioning of the frontline extension system.